The summer I turned pretty / Jenny Han. - Han, Jenny (Penguin Books, 2022)
Every year Isabel spends a perfect summer at her family friends' house. There's the swimming pool at night, the private stretch of sandy beach - and the two boys. Unavailable, aloof Conrad - who she's been in love with forever - and friendly, relaxed Jeremiah, the only one who's ever really paid her any attention.